Παιδιά με Μαθησιακές Δυσκολίες και Παιδιά Μειονοτήτων Κοινά Προβλήματα στη Μαθηματική Εκπαίδευση; - Σταθοπούλου Χαρούλα (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
We are presenting here the difficulties that minority students and students with learning difficulties face while learning mathematics. Specifically, we deal with students with learning difficulties, with minority students, and especially minority student with learning difficulties students coming from linguistic minorities and facing learning difficulties concerning mathematics. Teaching methods that could possibly improve the performance of those students are further investigated while at the same time the need for research in this field focusing on the Greek framework is pin-pointed.